PERSONAL BRANDING DALAM MEDIA SOSIAL: STUDI PADA MAHASISWA PENGUNJUNG MUSEUM MACAN - Aziz, Davi Ravindra (Emerging Markets : Business and Management Studies Journal, 2019)
The technology of internet is keep developing which led to a variety of socialmedia which is currently often used by teenagers, especially collegestudents. Social media has become a new platform for college tudents to dopersonal branding activities, especially in Instagram. The aim of thisresearch was to find out the process of personal branding in the social mediaconducted by visitors in Museum MACAN. The concepts of this research aresocial media, personal branding, and youth. Data collection and informationobtained through in-depth interviews with two informants who fit thecriteria. The results of this study was that the two informants had their ownway of building their personal branding and this affects them on maintaintheir accounts such as pay attention on likes given, numbers of followers,and other accounts they are followed. The second reason for this informantto visit the Museum MACAN was based on the same thing which they wantto follow the trend.